Eight gene mutation-based polygenic hazard score as a potential predictor for immune checkpoint inhibitor therapy outcome in metastatic melanoma - Zhao, Liqin; Luo, Ting; Jiang, Jinling; Wu, Junwei; Zhang, Xiaowei (Frontiers in Molecular Biosciences, 2022)
Background: Immune checkpoint inhibitor (ICI) therapies have revolutionized the treatment of metastatic cutaneous melanoma, but only benefit a subset of them. Genes mutation were reported to impact the ICI therapies outcome in metastatic melanoma but not been fully investigated. Hence, we systematically analyzed the impact of cancer related genes mutation on clinical outcome in metastatic melanoma patients underwent ICI therapies. Methods: Publicly available discovery and validation cohorts (312 patients and 110 patients respectively, all the patients received ICI therapies) were included in this study. Cox proportional hazards regression was used to assess the association of the 468 cancer related genes mutation with overall survival (OS) in the discovery cohort, and polygenic hazard score (PHS) were constructed subsequently, and validated in the validation cohort. The Tumor Immune Estimation Resource (TIMER) online tools, which was based on The Cancer Genome Atlas database, were used to analyze the impact of gene mutation on tumor-infiltrated immune cells in melanoma samples. Results: We found eight genes mutation were significantly associated with overall survival (BAP1, CARD11, IGF1R, KMT2D, PTPRD, PTPRT, ROS1, TERT, P < 0.05, mutation frequency >0.05). The PHS, which was based on these genes, was found to effectively discriminate the subset who benefited most from ICI therapies (HR=1·54, 95%CI, 1.25-1.95; P < 0.001). After adjusted with age, sex, ICI regimes, and tumor mutation burden (TMB), we found that PHS was an independent predictor for ICI therapies outcome (adjusted HR= 1.84, 95%CI, 1.22-2.79; P = 0.004). The PHS was validated in the validation cohort (log-Rank P = 0.038). Further research found that CARD11 and PTPRD mutation was significantly associated with more tumor-infiltrated immune cells in melanoma samples. Conclusion: For the first time, we have shown that PHS can independently and effectively predict the ICI therapy outcome in metastatic melanoma, which once validated by larger research, may help the decision-making in melanoma.